1999
DOI: 10.1007/s003830050624
|View full text |Cite
|
Sign up to set email alerts
|

Giant intra-abdominal cyst in a 13-year-old girl

Abstract: A case of a massive unilocular intra-abdominal cyst arising in a 13-year-old girl is presented. This appeared to be a foregut duplication cyst of gastric origin, and thus one of the largest recorded in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…However, none of these symptoms are specific for GD. In our study, the largest GD was found in a 13-year-old girl with the longest diameter of 40 cm on the greater curvature of the stomach, which was reported by M. Davenport in 1999 [ 43 ]. The symptom of this girl was gradual abdominal distention without abdominal pain and vomiting, and the lesion was successfully resected with uneventful recovery.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…However, none of these symptoms are specific for GD. In our study, the largest GD was found in a 13-year-old girl with the longest diameter of 40 cm on the greater curvature of the stomach, which was reported by M. Davenport in 1999 [ 43 ]. The symptom of this girl was gradual abdominal distention without abdominal pain and vomiting, and the lesion was successfully resected with uneventful recovery.…”
Section: Discussionsupporting
confidence: 69%
“…Clinical findings in patients with duplications include recurrent abdominal pain, vomiting, melena, abdominal distension, recurrent pancreatitis, weight loss, gastric outlet obstruction and failure to thrive, which is similar with the previous studies [ 1 , 27 ]. These symptoms may be caused by mucosal ulceration, increased pressure of GD cyst and pancreatic ducts involvement [ 43 , 44 ]. Symptoms of abdominal pain, weight loss and abdominal distension were seen more frequently in older patients, while vomiting and gastrointestinal hemorrhage were more common in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation